Early retirement behaviour in the Netherlands: evidence from a policy reform - Rob Euwals; Daniel van Vuuren (Institute for the Study of Labor (IZA), 2006)
In the early 1990s, the Dutch social partners agreed upon transforming the generous and actuarially unfair PAYG early retirement schemes into less generous and actuarially fair capital funded schemes. The starting dates of the transitional arrangements varied by industry sector. In this study, we exploit the variation in starting dates to estimate the causal impact of the policy reform on early retirement behaviour. We use a large administrative dataset, the Dutch Income Panel 1989-2000, to estimate hazard rate models for early retirement. We conclude that the policy reform induced workers to postpone early retirement. In particular, both the price effect (reducing implicit taxes) and the wealth effect (reducing early retirement wealth) are shown to have a positive impact on the early retirement age. Yet, we show that model specifications including the most commonly used financial incentive measures are open to further improvements, given that these are outperformed by a simple specification with dummy variables.
Keywords: C41; D91; J26; 330; early retirement; intertemporal choice; duration analysis; Alterssicherung; Flexible Altersgrenze; Reform; Zeitpräferenz; Niederlande; Ökonometrisches Modell